Pemberdayaan Keluarga dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) untuk Asuhan Komplementer Kebidanan - Wijaya, Ayu Wijaya; Nelly Nugrawati; Adam, Andi Muhammad; Zulkarnain, Zulkarnain (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2025)
This community service activity aimed to empower families in utilizing Family Medicinal Plants (TOGA) as a form of complementary midwifery care. The method used was interactive lectures combined with discussion, basic demonstrations, and structured interviews with five key informants, including a village midwife, health cadres, and housewives. The interviews revealed that public knowledge about TOGA remained traditional and unstructured, but there was strong enthusiasm for developing home TOGA gardens. Informants viewed TOGA as an affordable, accessible natural alternative, especially for minor complaints in maternal and child health. The main barriers identified were limited practical knowledge and the availability of plant seeds. This activity successfully increased community understanding and motivation to apply TOGA independently and appropriately. It also opened opportunities for forming village-based TOGA communities. The program is expected to be continued through cross-sector collaboration to strengthen health practices rooted in local wisdom